RELATIONS BETWEEN HUMAN RIGHTS AND PUBLIC POLICY: A MULTI-CASE STUDY OF THE IMPACT OF THE RECOMMENDATIONS OF THE INTER-AMERICAN COMMISSION ON HUMAN RIGHTS (Revista Direito em Debate, 2020)
The Inter-American Commission on Human Rights, which appears as one of the OAS organs for the promotion and protection of human rights, with its firm action ends up having significant effects on normative production and the development of public policies in favor of human rights of the Brazilian state.Such action derives from the attributions conferred upon them, in particular those related to the preparation of studies, reports and the proposition of recommendations to the States, as well as the adoption of measures that favor the system of protection of human rights at the domestic level and also as regards to the knowledge of individual petitions and interstate communications that contain denunciations of rights that have been debased.Although the reports issued by the Commission are not binding as they don’t have the legal nature of a decision, it is often noted that when a report is issued against a particular state that there has been a violation of human rights, it ends up employing efforts to change the situation in the country through legislative changes and public policies.The present study intends to analyze some consequences of the reports issued by the Inter-American Commission in face of the Brazilian State whose contrary manifestations count twenty incidences. However, for the purpose of this analysis, which will use the hypothetical-deductive method, where the impact of the recommendations on the internal legal order will be demonstrated, only three cases will be dealt with, since a time frame of the last ten years has been adopted.
Keywords: Inter-American Comission. Human Rigths. Public Policies. Brazil.